ANALYSIS FOR PERFORMANCE: SONATA NO 1 MOV I FANDANGOS Y BOLEROS KARYA LEO BROUWER - Ricky Oktariza Hermansyah (Jurnal Penelitian Musik, 2021)
This research departs from lack of criticality and interpretative phenomena in terms of music, especially classical guitar in Indonesia. As one example, the author analyzes of Sonata No.1 Mov. I. Fandangos y Boleros by Leo Brouwer. The purpose of this research is to analyze the fandango and bolero idioms as a consideration for interpretation. This discussion contains an analysis of the Spanish (fandango and bolero) and Cuban idioms found in Brouwer's work. The research method uses practice-led research, which in musical performances produces practical and textual results. The result of this research is that the folk music elements of fandango and bolero, varied and interspersed with elements of Afro-Cuban music and Brouwer's compositional style, are almost unrecognizable at first glance. However, after further investigation, it can be seen that in addition to the rhythmic elements of fandango and bolero, there is also a gradual increase in tempo and musical breaks that are characteristic of fandango and bolero music itself, or what Brouwer usually calls "stop motion" to create certain momentum after climax. With this research, it is hoped that it can increase the contribution in the field of music performance, especially classical guitar interpretation.